Interaction of novel benzanthrone derivative with amyloid lysozyme - Vus, K.O.; Trusova, V.M.; Gorbenko, G.P.; Zhytniakivska, O.A.; Kirilova, E.; Kirilov, G.; Kalnina, I. (Харьковский Национальный Университет им. В.Н.Каразина, 2011)
A novel benzanthrone derivative AM18 was investigated with respect to its photophysical properties when bound to native, oligomeric and fibrillar hen egg white lysozyme. As shown by fluorimetric titration AM18 is more sensitive to pathogenic protein aggregates than Thioflavin T, however has no ability to differentiate between mature and immature lysozyme fibrils. The recovered affinity and fluorescence response of the novel probe to amyloid protein appeared to be similar to those of recently developed amyloid lysozyme-sensitive dyes like e. g. Nile Red and cyanine dye 7515. Despite the high increase of the probe emission in the presence of amyloid lysozyme compared to its fluorescence in buffer, the minimal amount that could be detected by 1 μM AM18 was 10 times lower for amyloid-native protein solutions due to high affinity of the dye for lysozyme monomers. In general, because of high quantum yields and “signal-to-noise” ratios in the presence of pathogenic protein aggregates AM18 appeared to be an effective tool for amyloid detection and characterization in vitro, being however unable to detect pathogenic protein aggregates in vivo like e.g. recently reported p-FTAA because of the sensitivity to lipids. Compared to previously reported AM3 a novel dye showed 2-fold lower “signal-to- noise” ratio in the presence of fibrillar lysozyme, and 2 fold lower blue shift of emission maximum. This tendency was explained in terms of decreased charge transfer from the donor to acceptor groupes of AM18 compared to AM3. Finally, as concluded from the comparison of AM18 and previously studied benzanthrone derivatives, the 5 nm – red edge excitation shift of AM18 is indicative of its possible binding to fibril “deep cavities”, containing no water. High anisotropy values of amyloid-bound dye led us to conclusion that the enhanced fluorescence of the probe is associated with the decrease of the rotational motion of the amino-substitute about the benzanthrone unit. This is a sign of AM18 behaviour as a molecular rotor.
Keywords: amyloid marker; affinity; dye; fluorescence; lysozyme; specificity